Desain dan Implementasi MPPT PSO pada Sistem Pembangkit Listrik Tenaga - Diah Septi Yanaratri; Lucky Pradigta SR; Indra Ferdiansyah; Rachma Prilian Eviningsih (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Indonesia is a large archipelago country with various characteristic areas. Based on a report from the Ministryof Energy and Mineral Resources, Indonesia's electrification ratio has reached 98.86%. Even though Indonesia'selectrification ratio is close to 100%, it cannot be denied that there are still many remote areas that still do not haveelectricity supply. This can be caused by areas that are difficult to reach, thus hampering the construction of theelectricity network. To meet electricity needs in remote areas and with not too many population, a Diesel Power Plant(PLTD) is usually built, but this type of plant requires fuel oil which of course also requires replenishment everycertain time after the fuel runs out. To solve the above problems, a portable solar power plant (PLTS) is proposedwhich can be easily mobilized to facilitate delivery to remote areas. PLTS portable can also be used as an emergencypower source in areas where electricity facilities have been cut off due to natural disasters. To adjust the output voltageof the solar panels, a single input multi output (SIMO) converter topology is proposed. This converter consists of aflyback converter that can increase and decrease the voltage and has isolation between the input and output sides. Inaddition, this converter also has several outputs so that it can supply two loads (battery and communication equipment)at the same time. To maximize the conversion of solar energy in this system, it is also proposed to use the MPPTcontrol with the PSO method.